Production and characterization of carboxymethylcellulose from oil palm empty fruit bunch fibres / Rosnah Mat Soom - Mat Soom, Rosnah (2004)
Oil palm empty fruit bunch (EFB) is abundantly generated in the palm oil mill every year. The utilization of this oil residue as value-added products such as carboxymethylcellulose (CMC) could minimize the wastage and simultaneously provides additional income. Attempts to synthesize CMC from isolated cellulose of EFB were carried out. The EFB was first characterized and the findings showed that EFB constitutes of various components namely, the cellulose (39.5%), holocellulose (65.7%), oil (0.02%), extractive-free fibres (75.6%), extractives (6.9%), lignin (16.0%), ash (3.4%) and finally moisture (10.0%). Methods to isolate cellulose from the fibres were developed by adopting ASTM procedures that involved two major steps namely, delignifying of lignin and dissolution of hemicellulose. Trace amount of lignin (0.002%) were detected in cellulose that reflected the efficacy of the method developed and the cellulose was of high quality. The thermal behavior of cellulose analyzed by Perkin Elmer Pyris series — TGA 6 showed that it has the best heat resistance compared to EFB fibres and thus, reflected the crystalline feature of cellulose. The FTIR spectrum of cellulose analyzed by Perkin Elmer - FTIR Spectrum One Spectrophotometer was identical to the commercial cellulose. Method to produce CMC had been developed that involved manipulation of three variable parameters namely, temperature of reaction (55, 60 and 70°C), time of reaction (4, 6, 8, 16, 18 and 20 h) and concentration of sodium hydroxide (2.6 moles and 3.4 moles per mole of monochloroacetic acid). Thirty-six grades of CMC produced were characterized and the findings showed that the percent yield of CMC, moisture content, DS, purity, viscosity and ash content were in the range of 49.76 - 58.62%, 7.3 - 8.8%, 0.74 - 0.95, 85.5 - 99.5%, 116 - 2217 cps and 15.2 - 20.2%, respectively. Overall judgment on the selection of the best processing condition was preferably of 55°C, 2.6 moles NaOH and 4 h reaction time. The thermal profile of CMC showed the thermal stabilization of cellulose and the amorphous behavior of CMC. The FTIR spectra of CMC and commercial CMC exhibited similar pattern with the presence of peaks at the fingerprint region between 1300 — 1580 0111'1 due to the presence of carboxymethyl group. This clearly indicated that cellulose had been successfully converted to CMC.